Similar clinical outcome between patellar tendon and hamstring tendon autograft after anterior cruciate ligament reconstruction with accelerated, brace-free rehabilitation: a systematic review. Issue 6 (15th September 2017) - Janssen, Rob PA; van Melick, Nicky; van Mourik, Jan BA; Reijman, Max; van Rhijn, Lodewijk W
Abstract : Importance: Controversy exists with respect to the best graft choice for anterior cruciate ligament reconstruction (ACLR) with accelerated, brace-free rehabilitation. Objective: To investigate differences in clinical outcome between patellar tendon (PT) and hamstring tendon (HS) autografts for ACLR with accelerated, brace-free rehabilitation. Evidence review: Systematic review, all settings. Search from 1 January 1974 till 31 January 2017 in Medline (Pubmed), EMBASE (OVID), Cochrane Library and CINAHL according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. All study designs that reported clinical outcome in adults after arthroscopic, primary ACLR with accelerated, brace-free rehabilitation, HS or PT autografts were included. A risk of bias assessment of the eligible articles was determined. Data collection included surgical techniques, graft type, patient demographics, details of rehabilitation, patient-reported outcome, clinical outcome measures and radiological evaluation. A 'best-evidence synthesis' was performed for the formulated research questions. Eighteen studies were included. Findings: After autograft ACLR with accelerated, brace-free rehabilitation: (1) PT and HS autografts provide satisfactory short and long-term results in terms of range of motion, subjective stability and functional scores; (2) PT autograft is associated with more pain on kneeling and increased risk of knee osteoarthritis; (3) there is 'conflicting' evidence between PT and HS autografts for objective knee stability, knee laxity in females, return to sports and muscle strength; (4) there is no difference between males and females in return to sports irrespective of the chosen graft type; (5) HS autograft is correlated with tunnel widening; (6) early progressive eccentric exercises from 3 weeks postsurgery can safely be added irrespective of graft type; (7) early start of open kinetic exercises (4 weeks) causes increased laxity of HS autograft; (8) focus on quality of movement is important as part of ACL rehabilitation protocols and return to sports criteria. Conclusions and relevance: PT and HS autografts may both be selected for ACLR with accelerated, brace-free rehabilitation. Specific considerations for each graft type must be made during rehabilitation. PT reconstructions are more likely to result in statically stable knees, but are also associated with more complications and osteoarthritis. There is insufficient evidence to draw conclusions on differences between PT and HS autograft for long-term outcome. Level of evidence: III.